From political Islam to democrat Muslim: A case study of Rashid Ghannouchi's influence on ABIM, IKRAM, AMANAH and DAP - Malik, Maszlee (IIUM Press, 2017)
Rashid Ghannouchi has been known for his adherence to the idea of Islamic Democracy, which accepted democracy and its values as part of Islamic principles. For Muslims around the globe, Ghannouchi's non-conventional ideas are seen as something new and apt for the mdern democratic age, in particluar his recent epistemological departure from conventional 'Politcal Islam' to the paradigm of 'Democrat Muslim'. Ghannouchi's thoughts have been quoted by several Islamic organizations in Malaysia to legitimize their departure from the conventional Political Islamic discourse towards a more inclusive approach. Angkatan Belia Islam Malaysia (ABIM), Pertubuhan Ikram Malaysia (IKRAM) and Parti Amanah Negara (AMANAH) are examples of those who substantiated their departure from conventional legalistic Islamism discourse to the idea of Islamic democracy, freedom, power-sharing and continous dialogues and engagements with others through Ghannouchi's ideas. On the other hand, some leaders of the Democratic Action Party (DAP), a local secular party, have also been courting Ghannouchi. This study attemps to measure the influence of Rashid Ghannouchi's thoughts on the above mentioned organizations and parties and understand the motivations underlying the influence.